2011
DOI: 10.1089/end.2010.0233
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Single Flexible Ureteroscopy for Multiple Renal Calculi

Abstract: fURS is an effective treatment option in patients with multiple unilateral renal stones. Single procedure stone-free rates are high with a low rate of only minor complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…Score. The number of stones has been shown to be significant in other studies (21). A number of methods have been developed to describe stone burden by incorporating both the size and number of stones (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Score. The number of stones has been shown to be significant in other studies (21). A number of methods have been developed to describe stone burden by incorporating both the size and number of stones (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The number of stones has been shown to be significant in other studies (21). A number of methods have been developed to describe stone burden by incorporating both the size and number of stones (21,22). The description of total stone burden applies two dimensional measurements using rectangular and elliptical approximations (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances such as the miniaturization of the ureteroscopes, improvements of deflection and durability of flexible ureterorenoscopes as well as the improvement of stone disintegration using laser lithotriptors accordingly expanded the indications for URS to ureteroscopic treatment of larger-sized ureteral and kidney stones and multiple intrarenal stones, respectively [1,2,3,4,5,14,15,16,17,18,21]. However, ureteroscopy, especially when combined with laser lithotripsy, may cause severe complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of complications is stated to depend on various factors, such as stone size, stone width in ureteral stones, stone location, ureteral stone impaction and surgeon's or department's experience [8,9,10,11,12,13]. URS has also been successfully applied on larger-sized or multiple calculi of the upper urinary tract [14,15,16,17,18], which otherwise extends the duration of the URS procedure significantly. Longer duration of the URS procedure has however been shown to be strongly associated with ureteral perforation [10].…”
Section: Introductionmentioning
confidence: 99%
“…With PCNL and ESWL, there is also a need for multiple interventions for multiple renal stones in different locations. Although only a few studies have evaluated RIRS for the treatment of multiple renal stones, they have reported low interventions with high success rates (3,4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%